Polymerases Leave Fingerprints: Analysis of the Mutational Spectrum in Escherichia coli rpoB To Assess the Role of Polymerase IV in Spontaneous Mutation - Wolff, Erika (American Society for Microbiology, 2004)
We compared the distribution of mutations in rpoB that lead to rifampin resistance in strains with differing levels of polymerase IV (Pol IV), including strains with deletions of the Pol IV-encoding dinB gene, strains with a chromosomal copy of dinB, strains with the F′128 plasmid, and strains with plasmid amplification of either the dinB operon (dinB-yafNOP) or the dinB gene alone. This analysis identifies several hot spots specific to Pol IV which are virtually absent from the normal spontaneous spectrum, indicating that Pol IV does not contribute significantly to mutations occurring during exponential growth in liquid culture.